Ability of Extracts of Spirulina for the Removal of Arsenic from Isolated Liver Tissues of Experimental Rat (Journal of National Institute of Neurosciences Bangladesh, 2020)
Background: Spirulina has several effects in the metabolism of the body.Objective: The purpose of the present study was to see the ability of extracts of spirulina for the removal of arsenic from isolated liver tissues of rat.Methodology: This animal study was carried out on isolated liver tissues of Long Evans Norwegian adult healthy male rats weighing 160 to 200 g. The rats were 3 to 6 months of age obtained from animal house of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from 2004 to 2005. Measurements and all tasks were performed in a very careful manner. Atomic Absorption Spectrophotometer with Hydride Generator was used to measure the arsenic level. A set of freshly washed test tubes was taken. All test tubes contained 2ml tyrode solution and twenty small pieces of liver tissue maintaining 00C. No arsenic was added in test tube I. 2.5 μg/ml arsenic trioxide was added rest of the test tubes. They all were incubated for 45 minutes at 370C. Then the tissues were washed properly. The extracts of spirulina was added at 20 μl/ml dose. Second incubation was also for another 45 minutes at 370C. There were duplicates of all test tubes.Result: The effects of different extracts of spirulina (E1, E2, E4 and E7) on the removal of arsenic from arsenic loaded tissue were recorded. Amount of accumulated arsenic (mean ± se) in blank was 6.04 ± 3.05 μg/g of protein. After administration of 2.5 μg/ml arsenic trioxide in both incubation, the amount of accumulated arsenic was 245.02 ± 22.37 μg/g of protein. Blank was deducted from the standard and the value was considered as control and it was 238.96 ± 19.32 μg / g of protein. The arsenic loaded tissues were incubated with different extracts (E1, E2, E4 and E7) of spirulina in second incubation for another 45 minutes at 370C and each extract was for 20 μl / ml. After E1 extract of spirulina in second incubation, amount of accumulated arsenic was 136.40 ± 14.23 μg / g. There was 14.81% of removal of arsenic. Second incubation with E2 extract of spirulina (20 μl/ml) on arsenic loaded (2.5 μg/ml) tissue showed the amount of arsenic 242.56 ± 16.50 μg/g of protein (mean ± se). There was 12.59% of removal of arsenic.Conclusion: In conclusion extracts of spirulina has a significant ability to remove arsenic from isolated liver tissues of experimental rat.Journal of National Institute of Neurosciences Bangladesh, 2020;6(2): 105-109